Nomenclatural and taxonomic status of bird taxa (Aves) described by an ornithological swindler, Josef Prokop Pražák (1870–1904) - Mlíkovský, Jiří (Zootaxa, 2011)
Josef Prokop Pražák (1870–1904) published a number of papers from 1894–1900, mainly on faunistics and taxonomy of birds. In the 1890s his faunistic papers were shown to include many fraudulent data and were thus rejected or cited with caution. However, no comprehensive review of Pražák’s new bird taxa was made. My reconstruction of Pražák's Curriculum vitae shows that Pražák spent most of his life in his native Bohemia. In 1893–95 he studied at the Universität Wien, Austria, and volunteered at the Naturhistorisches Hofmuseum, and in 1896–98 he studied at the University of Edinburgh, Scotland. His taxonomic studies are connected with the ornithological collections in Vienna and Edinburgh. Although his contemporaries described Pražák as a charming and talented man, I document that his taxonomic papers include many fraudulent data and that his activities included stealing and relabeling museum specimens. The revision of Pražák's new bird taxa presented here reveals that Remizus and the following species-group names are available for nomenclatural purposes: Aegithalus caudatus japonica (Aegithalidae), Alauda arborea cherneli (Alaudidae), Carduelis elegans alpestris (Fringillidae), Carduelis elegans hortensis (Fringillidae), Carduelis elegans sylvestris (Fringillidae), Erithacus rubecula maior (Turdidae), Lophophanes cristatus brunnescens (Paridae), Lophophanes cristatus scotica (Paridae), Panurus biarmicus raddei (Paradoxornithidae), Parus caeruleus obscurus (Paridae), Parus major newtoni (Paridae), Parus major blanfordi (Paridae), Poecile cincta alascensis (Paridae), Poecile lugubris persica (Paridae), Remizus pendulinus raddei (Remizidae) and Sturnus vulgaris intermedius (Sturnidae). I defined type series for all, and I restricted type localities for most, of these species-group taxa. I synonymized Remizus pendulinus raddei Pražák, 1897g, with Remiz pendulinus pendulinus (Linnaeus, 1758). In addition I found that Vanellus grisescens was described by Grant (1912), not by Pražák, and I synonymized this species with Vanellus chilensis lampronotus (Wagler, 1827). I found that the following names created by Pražák have no standing in zoological nomenclature: Accentor modularis sclateri (hypothetical form), Anthus spipoletta reichenowi (hypothetical form), Scops scops taczanowskii (manuscript name), Trochalopteron hennickei (hypothetical form) and Vanellus grisescens (hypothetical form).